Pengaruh Latihan Hurdle Drill Terhadap Peningkatan Keterampilan Tendangan T Pada Atlet Pencak Silat - Sela Agustina; Raden Boyke Mulyana; Mulyana Mulyana (Jurnal Kepelatihan Olahraga, 2022)
Mastery of the T kick skill is a basic equipment that must be mastered by athletes in order to achieve achievement. This study aims to determine the effect of hurdle drill exercises on improving T kick skills in pencak silat athletes. Hurdle drill exercises are used to improve power, strength, speed, agility, balance, coordination, and help in improvising aspects of movement such as improving technical movement skills. The method used in this study is an experimental method using The One-Group Pretest-Posttest Design. The sample in this study was the athletes of the Student Achievement Pencak Silat Club (PSPP) as many as 16 athletes who were taken using the Total Sampling technique. The data collection technique was carried out by conducting an initial test and then given a hurdle drill exercise treatment by passing the hurdles, then a final test was carried out. The instrument used in this study is the T kick skill test. The results of the hurdle drill exercise have an effect on increasing the T kick skill. So it can be concluded that the exercise using the hurdle drill has a significant effect on improving the T kick skill in pencak silat athletes